A laboratory evaluation of nozzle tip damage in four generations of intraocular lens injector systems using a self-developed damage scale - Fang, Hui; Zhang, Lu; Schickhardt, Sonja; Merz, Patrick; Yan, Weijia; Leroux, Mélanie; Auffarth, Gerd U. (Scientific reports, 2022)
During intraocular lens (IOL) implantation it is not uncommon for the injector’s nozzle-tip to get damaged. However, the damage has not been systematically described or evaluated using an objective scale. In this study we developed our own system—the Heidelberg Score for IOL Injector Damage (“HeiScore”), which was used to grade 60 injectors from four generations of injector models (Monarch III D, AcrySert C, UltraSert, AutonoMe) made by the same manufacturer. (Alcon Laboratories Inc.) HeiScore has six grades of nozzle-tip damage: no damage (which was graded 0); slight scratches (1), deep scratches (2), extensions (3), cracks (4) and bursts (graded number 5). The score for each injector model was the sum of all grades (total number), and we could compare the four injector models. The injectors showed varying damage profiles, from “no damage” to “crack”. A tendency of a lower damage score in the newer generations of IOL injectors was noted. However, a statistically significant difference was observed only between Monarch III D and AutonoMe. The “Heidelberg Score for IOL Injector Damage” could efficiently and effectively evaluate the damage to IOL injector systems, which might help manufacturers optimize the positioning of the IOL in the injector during pre-loading.